Radiological study of C3–C4 level surgical cases of cervical spondylosis - Tomii, Masato; Mizuno, Junichi; Watanabe, Kazuo (Asian Journal of Neurosurgery, 2016)
Objective: The purpose of this study was to elucidate the pathological characteristics of C3-C4 cervical spondylotic myelopathy (CSM) from the radiological study. Materials and Methods: A total of 31 patients with single level anterior cervical discectomy and fusion (ACDF) at C3-C4 and 46 patients with single level ACDF at C5-C6 were included in this study. We selected C5-C6 level as a representative of the lower cervical level. The C3-C4 and C5-C6 levels were routinely examined to investigate the areas of the vertebral canal, subarachnoid space, and spinal cord in the cervical canal. Results: The clinical study of C3-C4 ACDF patients showed that as for the C3-C4 area, the area of the cervical vertebral canal, the area of the subarachnoid space, and he transverse surface area of the spinal cord were all significantly smaller in C3-C4 ACDF patients than in C5-C6 ACDF patients. Moreover, as for the C5-C6 area, only the area of the subarachnoid space was significantly smaller in C5-C6 ACDF patients than in C3-C4 ACDF patients. Spondylotic changes predominated at both the C3-C4 and C5-C6 levels. However, in the C5-C6 ACDF patients, spondylotic changes tended to predominate only at the operation level at C5-C6. Conclusions: Aging process develops from lower cervical to upper cervical level. Moreover, this static factor in conjunction with dynamic factor (instability) was the causative factors for the CSM in C3-C4 ACDF patients.
Keywords: Anterior cervical discectomy and fusion; C3-C4 level; cervical spondylotic myelopathy; static factor